A new genus and species of Edessinae from Amazon Region (Hemiptera: Heteroptera: Pentatomidae) - Fernandes, José Antônio Marin (Zootaxa, 2010)
The new genus Doesburgedessa is here proposed to include Edessa rugifera Stål, 1872 (type species) and four other species new to science: D. nigrolimbata sp. nov., D. armata sp. nov., D. elongatispina sp. nov., and D. linnei sp. nov. The new genus is characterized by a very unusual metasternal process with a single anterior projection that clearly derives from the bifurcated metasternal process found in Edessa. These species are restricted to the Amazon region; D. rugifera n. comb. is known from Brazil (Amazonas and Mato Grosso), D. nigrolimbata sp. nov. from Peru (Madre de Dios) and Bolivia (Santa Cruz), D. armata sp. nov. from Brazil (Pará and Mato Grosso), D. linnei sp. nov. from French Guiana (Cayenne and St Laurent du Maroni) and Guyana (East Berbice-Corentyne), and D. elongatispina sp. nov. from Brazil (Amazonas). The species were illustrated and photographed and the descriptions were made using external morphological characters, mostly from the metasternal process and the male and female genitalia.